Topical gels of etofenamate: in vitro and in vivo evaluation. (September 2015) - Marto, Joana; Baltazar, Diogo; Duarte, Aida; Fernandes, Adelaide; Gouveia, Luís; Militão, Maria; Salgado, Ana; Simões, Sandra; Oliveira, Eduardo; Ribeiro, Helena Margarida
Abstract Non-steroid anti-inflammatory drugs (NSAIDs), such as etofenamate, are among the most prescribed drugs used for their analgesic, anti-rheumatic, antipyretic and anti-inflammatory properties. Topical formulations have the main advantage of targeted delivery. However, drugs must overcome the skin due to its role as a physical and chemical barrier against the penetration of chemicals and microorganisms. This barrier must be altered to allow the permeation of drugs at a suitable rate to the desired site of activity. Permeation modulators can intercalate the skin outer layers causing structure disruption, opening an energetically favourable route for the drug to diffuse through. The aim of this work was the development of hydroalcoholic gels containing 5.0% (w/w) of etofenamate for topical administration with anti-inflammatory activity and enhanced drug delivery. The physical and chemical characterization, in vitro release and permeation studies and in vivo anti-inflammatory activity were assessed. The gel with 30% ethanol showed in vivo anti-inflammatory activity with suitable physical chemical and microbiologic characteristics. In vitro release and permeation studies revealed that the different amounts of ethanol used influenced the release profiles of etofenamate. Moreover, it was demonstrated that this formulation is an adequate vehicle for the etofenamate skin permeation.